The Law of the Iterated Logarithm in Analaysis - Ghimire, Santosh (Journal of the Institute of Engineering, 2014)
In this paper, we first discuss the history of the law of the iterated logarithm. We then focus our discussion on how it was introduced in analysis. Finally we mention different types of law of the iterated logarithm and state some of the recent developments. DOI: http://dx.doi.org/10.3126/jie.v9i1.10674 Journal of the Institute of Engineering, Vol. 9, No. 1, pp. 89–94